The partiality phenomenon in investigation of strength of the nervous system - Tadinac, Meri (1988)
The aim of this study was to test different hypotheses about the partiality phenomenon, which is usually described as the discrepancy between NSP diagnoses based on laboratory measures including different stimuli or responses. The correlation between the sensory and motor indices of nervous system strength within and between visual and auditory modality was investigated. The results show that different indices, with exception of motor measures related to different modalities, are not significantly correlated. The results are discussed in terms of the theory of basic nervous system properties, as the effect of (1) partial characteristics of separate analysers and/or (2) characteristics of peripheral parts of the analyzer and of the motor areas.
ENG